Dichotic turncoats: Lateralization of auditory processing in two dichotic listening tasks using melodies and syllables - Simon Knobloch; Philipp Haul; Saskia Rusche; Heiko Paland; Darius Zokai; Moritz Haaf; Jonas Rauh; Christoph Mulert; Gregor Leicht (PLoS ONE, 2025)
When confronted with dichotically presented syllables, right-handed healthy individuals tend to consciously perceive syllables presented to the right ear more often. This phenomenon, known as the right-ear advantage, is driven by delayed processing of information from the left ear in left temporal auditory cortex due to its indirect relay through the corpus callosum. In contrast, less is known about about the corresponding mechanisms for stimuli processed in the right temporal hemisphere. In this study, we developed a melody-based dichotic listening paradigm designed to induce a left-ear advantage. This novel paradigm, alongside a classical syllable-based paradigm was tested in 40 healthy right-handed participants. We also examined the influence of musical education on lateralization of auditory processing. Our results revealed a significant left-ear advantage for the perception of dichotically presented melodies and replicated established findings of a right-ear advantage for syllables. No group differences emerged between participants with or without current or past musical practice. However, among those with musical training, a greater number of years of practice was associated with a reduced right-ear advantage for syllables and an increased report of melodies presented to the left-ear. These findings suggest that the left-ear advantage in dichotic perception of melodies reflects right hemispheric processing of musical stimuli. Moreover, monitoring of the left ear seems to be altered by musical practice. Future research using neuroimaging techniques will be necessary to confirm this finding.